2017
DOI: 10.1108/pm-07-2016-0036
|View full text |Cite
|
Sign up to set email alerts
|

Increase in prices of farmland in the Czech Republic

Abstract: Purpose The purpose of this paper is to express the development of market price of farmland in the CR and to describe causes and effects of these changes in the price on the ownership of land in the country. Design/methodology/approach Primarily, description methods (especially for describing the creation of investment farmland funds) and a comparative analysis (in the case of an indicator of the farmland prices in the Czech Republic) were used in this paper. Findings The findings show that the situation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…In the past, farmers were not willing to offer real market prices to owners. But the situation has changed considerably in recent years, and many prosperous farmers are now willing to pay the adequate price for the land (Severova et al 2017). In addition, the price of land is also affected by the demand for long-term and speculative (short-term) non-agricultural investors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past, farmers were not willing to offer real market prices to owners. But the situation has changed considerably in recent years, and many prosperous farmers are now willing to pay the adequate price for the land (Severova et al 2017). In addition, the price of land is also affected by the demand for long-term and speculative (short-term) non-agricultural investors.…”
Section: Resultsmentioning
confidence: 99%
“…The development of agricultural land prices is modelled with the exponential trend also by Severova et al (2017). They showed that the average market price has increased from EUR 2 066 per ha in 2004 to EUR 5 956 per ha in 2015.…”
Section: Resultsmentioning
confidence: 99%
“…The findings made by Severová et al [63] show that the situation for agriculture in the Czech Republic has improved mainly due to the increase in subsidies; higher interest has been shown by non-agricultural entities, and banks are changing their attitude to granting loans for purchases of farmland.…”
Section: Market Price Of Land and Its Perspectivesmentioning
confidence: 99%
“…The reason is the effort to avoid the consequences of crop failures and grape price fluctuations. However, an important factor to be considered is the price of the farmland on which new vineyards are to be established, because "the value of farmland in the Czech Republic, together with its price, has increased significantly" (Severová et al, 2017).…”
Section: Wine Market In the Czech Republicmentioning
confidence: 99%